P.42: Estimation and Evaluation of Image Sticking on OLED Device. Issue 1 (1st July 2013) - Lim, Kyongho; Park, Sunhee; Lee, Don Gyou; Kim, Jaehong; Shin, Hongsoep; Park, Jongjin; Lim, Moojong
Abstract Image sticking and lifetime issues have been hot topics throughout the history of display devices. This paper describes the effect of the usage of contents to evaluate image sticking of display devices. Two different experiments were carried out to find the usage effect for different application such as mobile and TV using OLED products. The results show that the image sticking can be occurred in different time when different contents are applied to each display devices.